Born believers : the science of children's religious belief - Barrett, Justin L., 1971- (New York : Free Press, 2012)
In this book the author, a developmental psychologist and anthropologist, presents a theory that we are predisposed to believe in God from birth. It all begins in the brain. Infants, under the sway of powerful internal and external forces, make sense of their environments by imagining a creative and intelligent agent, a grand controller who makes the sun shine and the night fall. In the chaos of childhood, where so much is out of the child's control, this belief in a morally good creator can bring tremendous comfort and calm. A child's world is then filled with beings who intentionally act upon the environment, maintaining order. Summarizing scientific experiments conducted with children across the globe, the author illustrates the ways human beings have come to develop complex belief systems about God's omniscience, the afterlife, and the immortality of deities, and shows how this underlies all of the major world religions, uniting them under one common source.
On the train to Jaipur -- The evidence. Secret agents everywhere ; Children in search of a purpose ; Identifying the Maker ; The mind of God ; The nature of God -- The Implications. Natural religion ; It's okay to be childish ; So stupid they'll believe anything? ; Is atheism unnatural? ; Should you introduce children to God? ; Encouraging children's religious development.
Includes bibliographical references (pages 283-292) and index.
Keywords: Faith -- Psychology; God; Child psychology; Children -- Religious life; Psychology, Religious